Monstrous mothers : troubling tropes - Palko, Abigail L.; O'Reilly, Andrea, 1961- (Demeter Press, 2021)
"Motherhood is one of those roles that assumes an almost-outsized cultural importance in the significance we force it to bear. It becomes both the source of and the repository for all kinds of cultural fears. Its ubiquity perhaps makes it this perfect foil. After all, while not everyone will become a mother, everyone has a mother. When we force motherhood to bear the terrors of what it means to be human, we inflict trauma upon those who mother. A long tradition of bad mothers thus shapes contemporary mothering practices (and the way we view them), including the murderous Medea of Greek mythology, the power-hungry Queen Gertrude of Hamlet, and the emasculating mother of Freud's theories. Certainly, there are mother who cause harm, inflict abuse, act monstrously. Mothers are human. But mothers are also a favourite and easy scapegoat. The contributors to this collection explore a multitude of interdisciplinary representations of mothers that, through their very depictions of bad mothering, challenge the tropes of monstrous mothering that we lean on, revealing in the process why we turn to them. Chapters in Monstrous Mothers: Troubling Tropes explore literary, cinematic, and real-life monstrous mothers, seeking to uncover social sources and results of these monstrosities."--